Marine Mammals A Deep Dive into the World of Science - Brennecke, Dennis; Knickmeier, Katrin; Pawliczka, Iwona; Siebert, Ursula; Wahlberg, Magnus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This highly-readable Open Access textbook provides basic background information about marine mammals and anthropogenic impacts on them. The book includes inspiring exercises for education school programs in natural sciences. The book also provides advice on career paths using case studies of marine scientists and veterinarians describing their journeys from student to profession. By sharing real-life career paths, readers find answers to questions such as (3z(BWhat needs to be considered when choosing a career in science?(3y (Band (3z(BWhat kind of tasks do scientists undertake on a daily basis?(3y (BMarine mammals are amongst some of the most celebrated creatures on Earth, with their high intelligence, social and communicating skills, and capacity for deep diving. Alongside general information about marine mammals, the book aims at generating awareness of the impact of litter and noise pollution on the marine environment using marine mammals as an example. Huge numbers of marine animals,including marine mammals, die every year from entanglement in fishing gear, by ingestion of litter or because of chemical pollution. In the last decade many technological and scientific tools have been developed to aid research, for instance miniaturised sound recorders which can be attached to cetaceans and seals and record noise levels around them, their vocal production as well as their diving behaviour. This Open Access textbook can be used by undergraduate students interested in the fundamentals of marine mammal biology and medicine, and in pursuing the profession of a marine scientist. .s
Chapter 1. Who are the marine mammals? -- Chapter 2. Marine mammal acoustics -- Chapter 3. Whaling, seal culling, and the effect of fisheries on marine mammals -- Chapter 4. Plastic debris and its impacts on marine mammals -- Chapter 5. Chemical pollution and diseases of marine mammals -- Chapter 6. How to become a marine mammal scientist.
Keywords: Zoology; Veterinary medicine; Freshwater ecology; Marine ecology; Zoology; Veterinary Science; Freshwater and Marine Ecology